PENGARUH PADAT TEBAR TERHADAP KANDUNGAN ZAT GIZI IKAN LELE YANG DIPELIHARA DENGAN TEKNOLOGI BIOFLOK - Anang Suhardianto; Ariyanti Hartari (LPPM Universitas Terbuka, 2019)
This study aims to determine the effect of stocking density on the nutrient content of catfish that is cared with biofloc technology. Nutrients observed: 1) water content, 2) protein, 3) carbohydrates, 4) total fat, 5) saturated fatty acids / SFA, 6) monounsaturated fatty acids/ MUFA, 7) plural unsaturated fatty acids / PUFA , 8) omega-3, 9) omega-6, and 10) omega 9. Statistical tests on the 10 variables showed that stocking density did not have a significant effect on the 10 variables at a 5% confidence interval. Stocking density of treatment is 1000 heads/pond (T1), 2000 heads/pond (T2), 3000 heads/pond (T3), with a pond size of 2.0 m x height 1.0 m. Research results: 1. The average water content is 69.40–71.47% and the highest T3. 2. The protein content is 14.70-15.90%, the highest T2. 3. Carbohydrate content of 5.16-5.50%, the highest T2. 4. The average total fat content of 6.73-7.78%, the highest T1. 5. SFA content is around 43%, PUFA around 23%, and MUFA around 32%. 6. The highest omega-3 content is T3, then T1, and T2. Omega-6 and 9 sequence contents are T1, T2, and T3. It was concluded, the treatment of biofloc catfish stocking densities at a 5% confidence interval did not have a significant effect on the specified nutrient content. Penelitian ini bertujuan untuk menentukan pengaruh padat tebar terhadap kandungan zat gizi ikan lele yang dipelihara dengan teknologi bioflok. Zat gizi yang diamati: 1) kandungan air, 2) protein, 3) karbohidrat, 4) lemak total, 5) asam lemak jenuh/SFA, 6) asam lemak tak jenuh tunggal/MUFA, 7) asam lemak tak jenuh jamak/PUFA, 8) omega-3, 9) omega 6, dan 10) omega 9. Uji statistik terhadap ke-10 variabel menunjukkan padat tebar tidak memberikan pengaruh nyata terhadap ke-10 variabel pada selang kepercayaan 5%. Padat tebar perlakuan adalah 1000 ekor/kolam (T1), 2000 ekor/kolam (T2), 3000 ekor/kolam (T3), dengan ukuran kolam diameter 2,0 m x tinggi 1,0 m. Hasil penelitian: 1. Rata-rata kandungan air 69,40–71,47% dan T3 tertinggi. 2. Kandungan protein 14,70–15,90%, T2 tertinggi. 3. Kandungan karbohidrat 5,16–5,50%, T2 tertinggi. 4. Rata-rata kandungan lemak total 6,73–7,98%, T1 tertinggi. 5. Kandungan SFA sekitar 43%, PUFA sekitar 23%, dan MUFA sekitar 32%. 6. Kandungan omega-3 tertinggi T3, kemudian T1, dan T2. Omega-6 dan 9 urutan kandungannya T1, T2, dan T3. Disimpulkan, perlakuan padat tebar lele bioflok pada selang kepercayaan 5% tidak memberikan pengaruh yang nyata terhadap kandungan zat gizi yang ditentukan.